Pengaruh Pendidikan Agama Islam dalam Keluarga Terhadap Sikap Beragama Siswa - Sianipar, Bella Rosa; Siregar, Ratna; Siahaan, Peni; Syahfitri, Elvi Pradila (DIKLINKO JOURNALS PUBLISHER, 2023)
This type of research was a survey research and was a descriptive qualitative research. The population in this study were all students and parents of students. The technique used was sampling technique in Porposive Sampling ie the sample is taken directly that is class I, II, III which amounted to 134 students and the sample on the students was devoted to the learning process of Islamic Religious Education so directly to teachers who teach Islamic Religious Education. Further data collected in the field is processed by quantitative descriptive analysis. From the research results prove that, the influence of religious education in the family of religious attitudes toward students in Madrasah Aliyah Darunnajah Botong Kec. Bungaya Kab, Gowa presence of personality competencies owned by teachers of Islamic Religion and family, students can learn effectively and conducive atmosphere, be kind to teachers of Islamic Education and parents, students are able to receive lessons well so that students can increase their knowledge especially in the subjects of Islamic Religious Education which affect the character and behavior of students in the family.